Do hospital and rail accessibility have a consistent influence on housing prices? Empirical evidence from China - Chen, Kaida; Lin, Hanliang; Cao, Fangxiao; Han, Yan; You, Shuying; Shyr, Oliver; Lu, Yichen; Huang, Xiaodi (Frontiers in Environmental Science, 2022)
This study investigates the interaction between the accessibility of various public facilities and the price of urban space by analyzing the effect of hospital and rail accessibility on housing prices. In recent years, as the development of social civilisation and the impact of the COVID-19, people have become increasingly interested in the quality of healthcare in their living environment, resulting in the accessibility of hospitals in the city becoming a significant factor in the cost of a residence. At the same time, people tend to view rail travel as a means of accessing medical care; therefore, it is essential to demonstrate the intrinsic value of accessibility to hospitals and rail transportation in residential areas. As a point of reference, this paper presents an empirical analysis of Fuzhou, Fujian Province, China, a city in a developing nation with relatively widespread access to healthcare facilities and in the midst of a significant rail transit construction period. The study demonstrates that the interaction between hospital and rail accessibility moderates the effect on housing prices, and that this effect is geographically heterogeneous. The study also determines the optimal metric model for assessing geographical interaction based on the significance and stability of the interaction in geographic space. The study concludes with a discussion of the findings and social recommendations.